-3 + 3x = -2(x + 1)
First, regroup your terms. / Your problem should look like:
Second, expand. / Your problem should look like:
Third, add 3 to both sides. / Your problem should look like:
Fourth, simplify -2x - 2 + 3 to -2x + 1. / Your problem should look like:
Fifth, add 2x to both sides. / Your problem should look like:
Sixth, add 3x + 2x to get 5x. / Your problem should look like:
Seventh, divide both sides by 5. / Your problem should look like:
![x = \frac{1}{5}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B1%7D%7B5%7D%20)
Answer as fraction: x =
![\frac{1}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B5%7D%20)
Answer as decimal: x = 0.2